What should a learning health system look like? - Foy, Robbie; Carder, Paul; Johnson, Stella; Copsey, Bethan; Alderson, Sarah (BMJ open quality, 2025)
Correspondence to Dr Robbie Foy, University of Leeds, Leeds Institute of Health Sciences, Leeds, UK; r.foy@leeds.ac.uk Learning health systems have been defined as “a team, provider or group of providers in the health and care system that, working with a community of stakeholders, has developed the ability to learn from its own delivery of routine care and improve as a result”.1 The concept of learning health systems is gaining traction,2–4 including as a means of accelerating the translation of clinical evidence into practice. [...]the effectiveness of most implementation strategies is typically modest, although still potentially important at a population level. Learning health systems can combine repeated cycles of data-driven improvement with robust evaluation. [...]Reid et al recognise the need for five capabilities: advanced analytics and population insights; evidence synthesis and curation; patient, caregiver and provider co-design; implementation and reach; and rapid cycle evaluation, feedback and adaptation.4 We suggest several conditions necessary to establish a learning health system based on our experience and earlier work (box 1).22 Box 1 Suggested conditions for a learning health system Leadership and organisation Mutual stability to promote continuity in the partnership between healthcare system and researchers.